FAKTOR-FAKTOR YANG MEMPENGARUHI KASUS STUNTING PADA BALITA DI WILAYAH PAKUNIRAN - Mahsusiah, Windy Ayu Oktavil; Munir, Zainal; Sholehah, Baitus (NHM PRESS, 2024)
Background: Stunting is one of the nutritional problems in the world. Stunting occurs due to the impact of chronic malnutrition in the first 1000 days of a child's life. Parents play an important role in paying attention to their children's development and supporting efforts to overcome their children's nutritional problems. Preventing malnutrition in children starts with the mother, a mother's health is very important for the health of her child in the future, maternal malnutrition can disrupt the development of the fetus in the womb. Objective: To determine the factors that influence cases of stunting in toddlers. Method: This study used a cross sectional design, the population in this study was mothers who had stunted toddlers in the Pakuniran area, totaling 115 respondents. Bivariate data analysis used the Spearman test. Results: Of the several factors tested, there are 4 independent variables that are related to the dependent variable, namely; Early Marriage (P=0.000), Blood Supplement Tablets (P=0.000), Animal Protein (P=0.034), Antenatal Care Visit (P=0.011). Conclusion: it can be concluded that there is a significant relationship between early marriage, blood supplement tablets, animal protein, antenatal care visits on stunting cases in toddlers in the Pakuniran area. Suggestion: This research suggests that the government and health workers can provide counseling on a scheduled basis and in groups about the importance of preventing stunting in toddlers who are at risk of stunting.